Green Growth: Towards the Creation of Shared Value (International Journal of Scientific Research and Management (IJSRM), 2023)
Green growth promotes entrepreneurship with cutting-edge technology and advances in the modernization of production processes through the best use of company resources and preserving natural wealth. This manuscript aimed to know the Tehuacan businesspeople’s perceptions around green competitiveness in three dimensions: perception, experience, and management. The method was quantitative, non-experimental, cross-sectional, and descriptive, for which a research instrument was carried out to determine if they included actions related to climate change based on organizational management and focused on green growth. The findings around the three dimensions in the Phase 1 of the implementation model are that most of the companies are including climate change and green growth actions; however, they do not designate any investment for this purpose. The reasons to attend the climate change and green growth are the tax benefits, the relevant information procurement and technological assistance. Furthermore, the main consequences around green growth are regulatory compliance, financial performance, and positive corporate reputation. In the same sense, it is necessary to perform the other phases of the model and apply this model in other cultures and with different sort of enterprises.